Management of multiple sclerosis in women - Rice, G; Ebers, G (1995)
Multiple sclerosis is a disease of unknown origin, diverse effects, and uncertain prognosis. Treatment is primarily symptomatic and can be complicated by overly optimistic reports about improperly tested agents. Given these factors and the disease's erratic course, the primary care physician can provide ongoing medical referral and reliable information over the long term.